Capital as Death Denial - Sandy Brian Hager (Clickbait Capitalism: Economies of Desire in the Twenty-First Century, 2023)
Terror Management Theory (TMT) argues that subconscious fears about death shape our behaviour in often disturbing and destructive ways. Building on the work of Ernest Becker, the core theoretical claim of TMT is that human activity, including all forms of culture, is `…designed largely to avoid the fatality of death, to overcome it by denying in some way that it is the final destiny of man.' *** Capitalism is unlike anything that preceded it, and this novelty stems from a specific behaviour amongst capitalists that leads to sustained growth: the routine reinvestment of profits in the anticipation of future profitability. What might this novel feature of capitalism have to do with death denial? What kind of phenomenological specificity is bound up with this historical specificity? My aim in this chapter is to tackle these questions, primarily through a comparison between the role of death in capitalism and the archaic gift economy. *** My argument can be summarised as follows. First, I place the archaic gift economy, organised around the redistribution and destruction of surplus, on the low end of the death denial continuum. Archaic economic activity is collective and sacred, actively involving the dead and death in order to make payable the existential debts that haunt us from the moment of biological birth. Cyclical time and periodic redemptive ritual are purposefully designed to prevent accumulation of anything, whether it be wealth, power, time, anxiety, or guilt. Second, I place the capitalist economy, organised around the routine reinvestment of surplus for profit, on the high end of the death denial continuum. With capitalism, economic activity is individualised and de-sacralised and the dead and death are banished, resulting in unpayable debts. Capital accumulation is the primary psychological defence mechanism, a power intended to stave off mortal dread. But because accumulation rests on linear time and is shorn of redemptive and sacrificial ritual, guilt and anxiety also start to accumulate. The system is driven by an endless and increasing neurotic charge. Third, I claim that since the 1970s, capitalist death denial has intensified. Structural transformations in the so-called `advanced' economies over the past few decades have dissolved the remaining vestiges of collectivism in economic life and shattered any shared vision of social progress. The result is a disintegration of the remaining collective outlets needed to share, expiate, and to some extent relieve, the cumulative guilt and anxiety of capitalist life. Intensified death denial in the contemporary era finds its most spectacular manifestation in Silicon Valley's quest for literal immortality. This privatised immortality project is a morbid escapism intended to hive the ruling class off from the irredeemable masses.
Keywords: P; P1; 330; capital accumulation; death denial; fear of death; gift economy; immortality; Terror Management Theory